2021
DOI: 10.1002/med.21808
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming challenges of HERG potassium channel liability through rational design: Eag1 inhibitors for cancer treatment

Abstract: Two decades of research have proven the relevance of ion channel expression for tumor progression in virtually every indication, and it has become clear that inhibition of specific ion channels will eventually become part of the oncology therapeutic arsenal. However, ion channels play relevant roles in all aspects of physiology, and specificity for the tumor tissue remains a challenge to avoid undesired effects. Eag1 (K V 10.1) is a voltage-gated potassium channel whose expression is very restricted in healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 230 publications
(585 reference statements)
2
22
0
Order By: Relevance
“…Recently, researchers have turned to hiPSC-derived-CMs as an excellent alternative and a more reliable tool in the earliest stages of drug development to detect side effects of a new potential therapeutic agent that may cause prolongation of the QT interval before it is used in animal studies and clinical trials [ 323 ]. In addition, hiPSC allows us to study the behavior of ion channels in real CMs rather than in cell lines that are not myocytes and overexpress the potassium channel because of the response to compounds tested with hiPSC-derived-CMs in vitro is similar to that of the human body [ 324 ]. The effects of new drugs can be assessed in several ways, including electrophysiological responses using microelectrode arrays (MEAs), patch-clamp, or Ca 2+ oscillation measurements.…”
Section: Drug Testing and Drugs Development Using Hipsc-derived-cmsmentioning
confidence: 99%
“…Recently, researchers have turned to hiPSC-derived-CMs as an excellent alternative and a more reliable tool in the earliest stages of drug development to detect side effects of a new potential therapeutic agent that may cause prolongation of the QT interval before it is used in animal studies and clinical trials [ 323 ]. In addition, hiPSC allows us to study the behavior of ion channels in real CMs rather than in cell lines that are not myocytes and overexpress the potassium channel because of the response to compounds tested with hiPSC-derived-CMs in vitro is similar to that of the human body [ 324 ]. The effects of new drugs can be assessed in several ways, including electrophysiological responses using microelectrode arrays (MEAs), patch-clamp, or Ca 2+ oscillation measurements.…”
Section: Drug Testing and Drugs Development Using Hipsc-derived-cmsmentioning
confidence: 99%
“…Validation of the final merged K V 10.1 structure-based pharmacophore model was performed by screening against two libraries. The first library contained 15 compounds with known IC 50 values for K V 10.1 inhibition and a known binding site in the channel pore (Supporting Information Table S1) [17]. The second library contained compounds ('decoys') that are not likely to inhibit K V 10.1.…”
Section: Virtual Library Preparationmentioning
confidence: 99%
“…Ligands that have been reported to inhibit K V 10.1, but where the mechanism of action is not through the block of the potassium ion flux by binding to the central cavity of the channel, should therefore not fit our pharmacophore model. Our model was tested on such a virtual library (Supporting Information Table S3) that was constructed from ligands collected in a review article [17], with the addition of our newly identified set of K V 10.1 inhibitors [53]. The pharmacophore model identified 16 of 61 active compounds.…”
Section: Creation Of the Merged Structure-based Pharmacophore Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Ether à‐go‐go (Eag1) channels, a subtype of voltage‐dependent potassium channels, have also been shown to be important in the development of cancer types such as prostate, melanoma, breast, neuroblastoma and cervical cancer by associating it with cell proliferation (Bernal‐Ramos et al., 2017; Farias et al., 2004; Meyer & Heinemann, 1998; Meyer et al., 1999; Ouadid‐Ahidouch et al., 2001). These studies show that Eag1 channels can be used as biomarkers for early diagnosis of cancer and as new targets for cancer treatment (Rodríguez‐Rasgado et al., 2012; Toplak et al., 2021).…”
Section: Introductionmentioning
confidence: 99%